Anti-Infective and Anti-Inflammatory Mode of Action of Peptide 19-2.5 - Heinbockel, Lena (Int J Mol Sci, 2021)
The polypeptide Pep19-2.5 (Aspidasept(®)) has been described to act efficiently against infection-inducing bacteria by binding and neutralizing their most potent toxins, i.e., lipopolysaccharides (LPS) and lipoproteins/peptides (LP), independent of the resistance status of the bacteria. The mode of action was described to consist of a primary Coulomb/polar interaction of the N-terminal region of Pep19-2.5 with the polar region of the toxins followed by a hydrophobic interaction of the C-terminal region of the peptide with the apolar moiety of the toxins. However, clinical development of Aspidasept as an anti-sepsis drug requires an in-depth characterization of the interaction of the peptide with the constituents of the human immune system and with other therapeutically relevant compounds such as antibiotics and non-steroidal anti-inflammatory drugs (NSAIDs). In this contribution, relevant details of primary and secondary pharmacodynamics, off-site targets, and immunogenicity are presented, proving that Pep19-2.5 may be readily applied therapeutically against the deleterious effects of a severe bacterial infection.